Vitamin C exerts anti-cadmium induced fracture functions/targets: bioinformatic and biostructural findings - Rong Li; Songzuo Yu; Xiao Liang; Yu Li; Keng Po Lai (Food Science and Human Wellness)
Background: Epidemiological data indicate an association between cadmium exposure and risk of bone fracture; however, clinical treatment of cadmium-induced fracture is limited. Although vitamin C (VC) reportedly reduces cadmium-induced fracture, its pharmacological mechanism remains unexplored. Methods: Thus, we used a network pharmacology approach and molecular docking analysis to identify core targets, functional processes, and biological pathways involved in the anti-fracture action of VC. Results: Bioinformatics identified 17 intersection targets of VC and cadmium-induced fracture. Nine core targets were characterized, including tumor protein p53, epidermal growth factor receptor, proto-oncogene c, mitogen-activated protein kinase-1 (MAPK1), MAPK3, signal transducer and activator of transcription-3, MAPK14, prostaglandin-endoperoxide synthase 2, and estrogen receptor alpha. Interestingly, findings of molecular docking analysis indicated that VC exerted effective binding capacity in cadmium-induced fracture. Furthermore, biological processes, cell components, molecular functions, and pharmacological pathways involved in the action of VC against cadmium-induced fracture were identified and visualized. Conclusions: Based on these findings, we conclude that VC exhibits its anti-cadmium-induced fracture effects by promoting osteoblastic regeneration and proliferation, and inhibiting inflammatory stress. The core targets may serve as biomarkers for diagnosing cadmium-induced fractures.